Spider Bite: A Rare Case of Acute Necrotic Arachnidism with Rapid and Fatal Evolution. (29th August 2016) - Pezzi, Mario; Giglio, Anna Maria; Scozzafava, Annamaria; Filippelli, Orazio; Serafino, Giuseppe; Verre, Mario
Abstract : The spider bites are quite frequent and often resolve quickly without leaving outcomes; only some species are capable of causing necrotic and systematic lesions in humans. Among them, we should mention the genus Loxosceles . The venom released from the spider bite of Loxosceles species is composed of proteins, enzymes, and nonenzymatic polypeptides. The phospholipase D family was identified as the active component of the venom. This family of enzymes is responsible for the local and systemic effects observed in loxoscelism. Phospholipases D interact with cell membranes triggering alterations which involve the complement system and activation of neutrophils and they cause the dermonecrotic skin lesions and systemic effects. We describe a fatal case of acute intoxication caused by a spider bite probably belonging to the species Loxosceles . The initial lesion was localized to a finger of a hand. Clinical course was worsening with deep necrotic lesions on limb, shock, hemolysis, acute kidney failure, and disseminated intravascular coagulation. All therapies were ineffective. This is the first fatal case described in Europe.